Neuropathophysiological Mechanisms and Treatment Strategies for Post-Traumatic Epilepsy - Muhammad Munwar Ali, Muhammad Asif Khaskheli, Inayatullah Awan, Khairunisa Shaikh, Safdar Hussain Arain, Abrar Shaikh (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To understand and analyze neuropathophysiological mechanisms and treatment strategies for post traumatic epilepsy. Study design: Cohort clinical trial study Place and duration of study: Department of Neurosurgery, Chandka Medical College Hospital, Larkana 1st January 2021 to 31st March 2022. Methodology: One hundred and twenty cases of traumatic brain injury were enrolled. In 1st sub group there was 20 cases were given either Sodium valproate (SG1a) while 20 were given its placebo (SG1b). Similarly in subgroup 2nd and 3rd, each had 20 cases who were given Levetiracetam (SG2a) or Phenytoin (SG3a) respectively or other given its respective placebo (n=20/SG2b, SG3b). Primary and secondary outcomes were measured. Results: The mean age was 30.1±3.3 years. There was almost equal number of both genders with slightly higher number of males than females with no significant variance. Around 40.83% of the cases were suffering from traumatic brain injury as a result of fall from a higher/raised building or structure. Conclusion: The sodium valproate had a highest efficacy in controlling of the post-traumatic brain injury epileptic seizure not only for a short duration but for longer duration as well. Keywords: Treatment strategies, Post-traumatic epilepsy, Neuropathophysiological mechanisms